GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 15 Oct 2019, 16:49

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# M28-03

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 58340

### Show Tags

16 Sep 2014, 01:28
00:00

Difficulty:

35% (medium)

Question Stats:

66% (01:12) correct 34% (01:35) wrong based on 174 sessions

### HideShow timer Statistics

If $$x\neq{y}$$ and $$y = \frac{x^2 - y^2}{x-y}$$, then what is the value of $$y$$?

(1) $$x+y-3=0$$

(2) $$x(y-3)=0$$

_________________
Math Expert
Joined: 02 Sep 2009
Posts: 58340

### Show Tags

16 Sep 2014, 01:28
1
Official Solution:

Given $$y = \frac{x^2 - y^2}{x-y}$$. Simplify: $$y = \frac {(x - y)(x+y)}{x-y}$$. Reduce by x-y: $$y=x+y$$. So, we have that $$x=0$$.

(1) $$x+y-3=0$$. Since $$x=0$$, then $$y=3$$. Sufficient.

(2) $$x(y-3)=0$$. Since $$x=0$$, then $$y$$ can take ANY value. Not sufficient.

_________________
Intern
Joined: 02 Feb 2017
Posts: 15
Concentration: Entrepreneurship, Strategy

### Show Tags

14 Jun 2017, 07:49
If x≠yx≠y and y=x2−y2x−yy=x2−y2x−y, then what is the value of yy?
(1) x+y−3=0x+y−3=0
(2) x(y−3)=0

I am not so sure for statement 2.
If x(y−3)=0
They x=0 or y=3
If x=0, they y=0. As per question If x≠y, so y cannot be 0.
Not sure whats wrong with my logic.
Any expert can explain.
ThankS
Intern
Joined: 08 Feb 2017
Posts: 6

### Show Tags

19 Jul 2017, 09:01
Given y=x2−y2x−yy=x2−y2x−y. Simplify: y=(x−y)(x+y)x−yy=(x−y)(x+y)x−y. Reduce by x-y: y=x+yy=x+y. So, we have that x=0x=0.

(1) x+y−3=0x+y−3=0. Since x=0x=0, then y=3y=3. Sufficient.

(2) x(y−3)=0x(y−3)=0. Since x=0x=0, then y can take ANY value. Not sufficient.

regarding point two .
i did not understand why Y can take any value ? .
(y-3) has to be equal to zero ?
Math Expert
Joined: 02 Aug 2009
Posts: 7957

### Show Tags

19 Jul 2017, 09:14
1
ashimd wrote:
Given y=x2−y2x−yy=x2−y2x−y. Simplify: y=(x−y)(x+y)x−yy=(x−y)(x+y)x−y. Reduce by x-y: y=x+yy=x+y. So, we have that x=0x=0.

(1) x+y−3=0x+y−3=0. Since x=0x=0, then y=3y=3. Sufficient.

(2) x(y−3)=0x(y−3)=0. Since x=0x=0, then y can take ANY value. Not sufficient.

regarding point two .
i did not understand why Y can take any value ? .
(y-3) has to be equal to zero ?

Hi statement 2 says x(y-3)=0..
If x=0, y-3 can be anything including 0 because 0*(y-3) will always be 0 irrespective of value of y-3..
But if x is Not EQUAL to 0, y-3 has to be 0...
_________________
Thread Master - Part Time MBA Programs
Joined: 11 Jan 2018
Posts: 145

### Show Tags

11 Oct 2018, 07:53
This is a great question!

I chose D, because my approach for the 2) was

=X(Y-3)=0
= Xy-3x = 0
= xy = 3x
y=3

But I found why I was wrong.
Manager
Status: Single
Joined: 02 Jan 2016
Posts: 175
Location: India
Concentration: General Management, Accounting
GMAT 1: 730 Q49 V40
GPA: 4
WE: Law (Manufacturing)

### Show Tags

15 Nov 2018, 19:49
I did exactly the same way... hanamana

=X(Y-3)=0
= Xy-3x = 0
= xy = 3x
y=3

Is it because we know from stem that X = 0 and 0/0 is undefined ?

But its not explicitly given in the question stem ?

can you me your opinion on this ? and Bunuel chetan2u Sirs ?
Math Expert
Joined: 02 Sep 2009
Posts: 58340

### Show Tags

15 Nov 2018, 23:19
hero_with_1000_faces wrote:
I did exactly the same way... hanamana

=X(Y-3)=0
= Xy-3x = 0
= xy = 3x
y=3

Is it because we know from stem that X = 0 and 0/0 is undefined ?

But its not explicitly given in the question stem ?

can you me your opinion on this ? and Bunuel chetan2u Sirs ?

From the stem (after we simplified given equation $$y = \frac{x^2 - y^2}{x-y}$$) we got that x = 0. Since we cannot divide by 0, then you cannot divide xy = 3x by x to get y = 3. Basically for (2) we have that 0(y - 3) = 0. Now, 0(y - 3) is 0 regardless of the value of y.
_________________
Intern
Joined: 02 Jan 2018
Posts: 4

### Show Tags

26 Jan 2019, 21:22
I think this is a poor-quality question and I don't agree with the explanation. For statement 2, if you know one of the values in an equation, you substitute and find the other value. (Basic of GMAT math). this explanation seems to violate that
Director
Joined: 09 Mar 2018
Posts: 996
Location: India

### Show Tags

26 Jan 2019, 23:44
Bunuel wrote:
If $$x\neq{y}$$ and $$y = \frac{x^2 - y^2}{x-y}$$, then what is the value of $$y$$?

(1) $$x+y-3=0$$

(2) $$x(y-3)=0$$

y = x-y * x+y / x-y

y = x + y

from this we can say x =0 but y can be any value, integer ,fraction or a number

(1) $$x+y-3=0$$
From here we get a definite value as y = 3
Sufficient

(2) $$x(y-3)=0$$[/quote]
Now, i didn't realize this initially

0 * (y-3) = 0

y can be any value > 3

3.1, 6 , 9, these values will satisfy the statement

But will give multiple values for the question what is the value of y

A

NEVER assume things.
_________________
If you notice any discrepancy in my reasoning, please let me know. Lets improve together.

Quote which i can relate to.
Many of life's failures happen with people who do not realize how close they were to success when they gave up.
Math Expert
Joined: 02 Sep 2009
Posts: 58340

### Show Tags

27 Jan 2019, 02:50
itsrahulmohan wrote:
I think this is a poor-quality question and I don't agree with the explanation. For statement 2, if you know one of the values in an equation, you substitute and find the other value. (Basic of GMAT math). this explanation seems to violate that

(2) $$x(y-3)=0$$. Since $$x=0$$, then $$y$$ can take ANY value. Not sufficient.

We want of find the value of y. Can you?
_________________
Intern
Joined: 04 May 2019
Posts: 4

### Show Tags

11 Jul 2019, 07:50
Hi for statement 2,
We do know x = 0, but..
Divide both sides by x
x(y−3)=0
=> x/x * (y-3) = 0/x
=> y-3 = 0
y = 3

Please tell me why we can't use this. Because x is zero from the stem, does it mean this method is invalid?
Math Expert
Joined: 02 Sep 2009
Posts: 58340

### Show Tags

11 Jul 2019, 07:56
1
Boltions wrote:
Hi for statement 2,
We do know x = 0, but..
Divide both sides by x
x(y−3)=0
=> x/x * (y-3) = 0/x
=> y-3 = 0
y = 3

Please tell me why we can't use this. Because x is zero from the stem, does it mean this method is invalid?

We cannot divide by 0.

(2) $$x(y-3)=0$$. Since $$x=0$$, then $$y$$ can take ANY value. Not sufficient.

Basically for (2) we have that 0(y - 3) = 0. Now, 0(y - 3) is 0 regardless of the value of y.
_________________
Intern
Joined: 04 May 2019
Posts: 4

### Show Tags

11 Jul 2019, 17:59
Thank you very much
Re: M28-03   [#permalink] 11 Jul 2019, 17:59
Display posts from previous: Sort by

# M28-03

Moderators: chetan2u, Bunuel